Epitopes as characterized by antibody-verified eplet mismatches determine risk of kidney transplant loss - Sapir-Pichhadze, Ruth; Zhang, Xun; Ferradji, Abdelhakim; Madbouly, Abeer; Tinckam, Kathryn J.; Gebel, Howard M.; Blum, Daniel; Marrari, Marilyn; Kim, S. Joseph; Fingerson, Stephanie; Bashyal, Pradeep; Cardinal, Héloïse; et al. (Kidney international, 2020)
To optimize strategies that mitigate the risk of graft loss associated with HLA incompatibility, we evaluated whether sequence defined HLA targets (eplets) that result in donor-specific antibodies are associated with transplant outcomes. To define this, we fit multivariable Cox proportional hazard models in a cohort of 118 382 United States first kidney transplant recipients to assess risk of death-censored graft failure by increments of ten antibody-verified eplet mismatches. To verify robustness of our findings, we conducted sensitivity analysis in this United States cohort and assessed the role of antibody-verified eplet mismatches as autonomous predictors of transplant glomerulopathy in an independent Canadian cohort. Antibody-verified eplet mismatches were found to be independent predictors of death-censored graft failure with hazard ratios of 1.231 [95% confidence interval 1.195, 1. 268], 1.268 [1.231, 1.305] and 1.411 [1.331, 1.495] for Class I (HLA-A, B, and C), -DRB1 and -DQB1 loci, respectively. To address linkage disequilibrium between HLA-DRB1 and -DQB1, we fit models in a subcohort without HLA-DQB1 eplet mismatches and found hazard ratios for death-censored graft failure of 1.384 [1.293, 1.480] for each additional antibody-verified HLA-DRB1 eplet mismatch. In a subcohort without HLA-DRB1 mismatches, the hazard ratio was 1.384 [1.072, 1.791] for each additional HLA-DQB1 mismatch. In the Canadian cohort, antibody-verified eplet mismatches were independent predictors of transplant glomerulopathy with hazard ratios of 5.511 [1.442, 21.080] for HLA-DRB1 and 3.640 [1.574, 8.416] for -DRB1/3/4/5. Thus, donor-recipient matching for specific HLA eplets appears to be a feasible and clinically justifiable strategy to mitigate risk of graft loss. [Display omitted]